2014
DOI: 10.1002/jbmr.2422
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Promote Osteoblastic Differentiation In Vivo: Implications in Fracture Repair and Bone Homeostasis

Abstract: Macrophages are activated in inflammation and during early phases of repair processes. Interestingly, they are also present in bone during development, but their function during this process is unclear. Here, we explore the function of macrophages in bone development, growth, and repair using transgenic mice to constitutively or conditionally deplete macrophages. Depletion of macrophages led to early skeletal growth retardation and progressive osteoporosis. By 3 months of age, macrophage-deficient mice display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
266
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(285 citation statements)
references
References 41 publications
19
266
0
Order By: Relevance
“…This finding is concurrent with the in vitro experiment indicating that the removal of macrophages diminished osteoblast mineralization (Chang et al, 2008). This decreased mineralization is probably associated with the lack of osteoblasts originated from macrophage-enhanced osteoblastic differentiation (Vi et al, 2015). Claudia et al have proven that M2 macrophage enhancement driven by IL-4 and IL-13 improved bone remodeling (Schlundt et al, 2015).…”
Section: Excreted Factorssupporting
confidence: 57%
“…This finding is concurrent with the in vitro experiment indicating that the removal of macrophages diminished osteoblast mineralization (Chang et al, 2008). This decreased mineralization is probably associated with the lack of osteoblasts originated from macrophage-enhanced osteoblastic differentiation (Vi et al, 2015). Claudia et al have proven that M2 macrophage enhancement driven by IL-4 and IL-13 improved bone remodeling (Schlundt et al, 2015).…”
Section: Excreted Factorssupporting
confidence: 57%
“…It has been reported that macrophages can convert to a pro-healing phenotype and promote limb generation [17]. Macrophages could also help maintain bone homeostasis and promote fracture healing by enhancing the differentiation process of mesenchymal progenitors [2]. Herein we inferred that macrophage aggregation would likely present in the femoral fracture area.…”
Section: Introductionmentioning
confidence: 93%
“…Further experiments are required to clarify this. A time sensitive effect was reported also in a shaft model where reduced macrophage numbers before the time of fracture had a stronger effect than if the reduction occurred 3 days after [51]. Similarly in a water salamander model where a foot was resected; regrowth of the limb was blocked permanently if clodronate liposomes were delivered before the surgery but not if the liposomes were injected at day 10 to 13.…”
Section: Inflammation Plays Different Roles In Cancellous and Corticamentioning
confidence: 90%